Study on Handing Process and Quality Degradation of Oil Palm Fresh Fruit Bunches (FFB) - Mat Sharif Z.B.; Mohd Taib N.B.; Bin Yusof M.S.; Bin Rahim M.Z.; Bin Mohd Tobi A.L.; Bin Othman M.S. (Institute of Physics Publishing, 2023)
Fruits; Surveys; Fresh fruits; Handling process; Harvesting activities; Malaysia; Oil palm; Quality degradation; Quantitative approach; Palm oil